EFECTIVENESS OF VIRUS MATERIAL TOPIC STUDENT WORKSHEET BASED ON KNOW-LEARNED (K-L) METACOGNITIVE STRATEGY TO TRAIN STUDENT METACOGNITIVE SKILLS - Savitri, Sonia; Susantini, Endang (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2019)
Metacognitive skill is essential for students. One of learning materials which can train metacognitive skillis worksheet based on metacognitive strategy. This research aimed to produce an effective studentworksheet based on Know-Learned (K-L) strategy on virus material topic to train student’s metacognitiveskill. This research which had been held in Biology Department, FMIPA, Unesa. This study was adevelopmental research which referred to 3-D model namely define, design, and develop. The researchstage started with define stage which conducted by analyzing curriculum on virus material. Thencontinued with design stage which conducted by designing and developing student worksheet. Studentworksheet consists of know-learned phase, which equipped with self-confidence level column, comparingconcept column, and score column, so it can facilitate students to practice monitoring and evaluationskills. Then at the develop stage, student worksheet implemented limitedly to fifteen 10thgrade studentsof SMAN 4 Sidoarjo. Finally, the effectiveness of student worksheet evaluated based on studentmetacognitive skill, completeness of indicators, and gain score. The research result showed that thestudent worksheet was effective with the student’s metacognitive score of 3.93 (very good category) andpositive sensitivity in the range of 0.3-1.0. In addition, student worksheet was also effective to gainlearning outcomes of 93.33% students with the high criteria and 6.67% student with the medium criteria.Therefore, student worksheet based on K-L metacognitive strategy was effective to train studentsmetacognitive skill and gain their learning outcomes at once on virus material.Keywords: worksheet, know-learned, metacognitive skill, virus material.